2018
DOI: 10.1051/matecconf/201821501027
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Fermentation of Banana Peels Potential Study for Feed Additive

Abstract: Agricultural solid wastes present abundantly on earth as crops harvesting as well as processing are countinuesly run. Banana peels are one of agricultural solid wastes produced anywhere the banana processing presents. The peels present abundantly in tropical countries such as Indonesia. The carbohydrate content of banana peels make it useful for the production of many chemicals, including feed. Meanwhile the large need in feed in farming including fish farming could prevent farmer to obtain substantial profit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Jaganmohan et al (2013) reported that Aspergillus terreus has a high protein value and can be a good choice for SCP production using Eichornia and banana peel as substrates [56]. Fatmawati et al (2018) used banana peel as substrate for production of single cell protein from Saccharomyces cerevisiae Y1536 and Rhizopus oryzae FNCC 6157 to be utilized as fish feed [57].…”
Section: Scp From Wastesmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaganmohan et al (2013) reported that Aspergillus terreus has a high protein value and can be a good choice for SCP production using Eichornia and banana peel as substrates [56]. Fatmawati et al (2018) used banana peel as substrate for production of single cell protein from Saccharomyces cerevisiae Y1536 and Rhizopus oryzae FNCC 6157 to be utilized as fish feed [57].…”
Section: Scp From Wastesmentioning
confidence: 99%
“…The SSF process skips elaborate prearrangements for media preparation. Currently, there is a worldwide interest for SCP production using SSF [ 47 , 56 , 57 , 63 , 64 , 67 , 96 ]. There is an active and ongoing research and development on SCP from various fungal species, which may result in innovative products or production processes.…”
Section: Single Cell Proteinsmentioning
confidence: 99%
“…Also, some research proved that R. oryzae has probiotic properties that are advantageous for poultry (Hamza & Gunyar, 2022; Sugiharto et al, 2015; Yudiarti et al, 2014). Many studies had positive results in converting poorly nutritious agro‐industrial by‐products into usable feed components through fermentation by R. oryzae strains (Fatmawati et al, 2018; Ibarruri & Hernández, 2018; Karimi et al, 2019; Kupski et al, 2012; Schmidt et al, 2014; Sugiharto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Each country or region finds the cheapest and most available agro‐industrial waste to study its efficiency as an unconventional feed ingredient, for instance, cassava and its by‐products were studied in Nigeria, Malaysia, Thailand and Indonesia (Aro, 2008; Khempaka et al, 2014; Ramin et al, 2011; Sugiharto et al, 2015), ground sago pith in Malaysia (Ab Jalil et al, 2014), banana peels, pineapple waste, palm kernel cake and rice bran in Indonesia (Fatmawati et al, 2018; Mandey et al, 2018; Yana Sukaryana, 2015), winery biomass wastes in Australia (Jin et al, 2016), Terminalia catappa fruit and Mangifera Indica Seed Kernels in Nigeria (Apata, 2011; Lawan Binta et al, 2018), rapeseed in India (Jannathulla et al, 2019), and seaweed in Korea (Choi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The fermentation process is being formulated globally as a supplementary diet for aquaculture development and production. Numerous fermented fibrous agricultural wastes, including papaya processing waste, apple pomace and banana peels have been _________________________________________________________________________________ employed as feed additives and immunostimulants for fish or shrimp (Fatmawati et al, 2018). This low-protein and high-carbohydrate agricultural waste can provide cheap fish energy.…”
mentioning
confidence: 99%